Identification of Dyscalculia in Children Special Needs for the Impaired Knowing Numbers - Nanda, Anggraeni Shafria Mega; Lutfiyah, Lutfiyah; Murtinasari, Frida (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
This study aims to identify and describe the difficulties in learning mathematics or dyscalculia experienced by children with special needs with disabilities in learning mathematics the subject of knowing numbers. The type of research used in this research is descriptive research with a qualitative approach. Research instruments include observation, tests, and interviews. The results obtained were that the S1 subject experienced the characteristics of dyscalculia which included difficulties in language and reading, abnormalities in visual perception disorders, perseveration, and disturbances in body perception. While subject S2 experienced the characteristics of dyscalculia, namely language and reading difficulties. This study concludes that S1 and S2 subjects were identified as having dyscalculia.